Discovering human diabetes-risk gene function with genetics and physiological assays - Heshan Peiris (Nature Portfolio, 2018)
The function of genes linked to type 2 diabetes is poorly characterized. Here the authors combine Drosophila genetics and physiology with human islet biology to identify new regulators of insulin secretion including BCL11A.